Manual de procedimientos para la Dirección del Centro Académico San José, Tecnológico de Costa Rica - Vindas-Corrales, Meilyn (Instituto Tecnológico de Costa Rica., 2016)
The Tecnológico de Costa Rica (TEC), was founded under law 4777 in June 10th 1971, as an autonomous national institution of higher education dedicated in teaching, investigation and the extension of science and technology for Costa Rica’s development. The CASJ direction was created to coordinate, supervise, and evaluate the tasks of the teachers as well as the investigation and extension performed, accomplishing the institutional goals. Therefore, it is needed a document that will contain the details of the procedures used in their daily work. The Procedures Manual was developed at the Direction of the Centro Académico San José, which is part of the structure of the Tecnológico de Costa Rica. The reason of the Project is to provide the CASJ Direction with a Procedures Manual trying to make more efficient the procedures performed. The study will show the gaps, and the steps of each procedure that are not as efficient as they could be or even the excess of steps in a task.
Proyecto de graduación (Bachillerato en Administración de Empresas) Instituto Tecnológico de Costa Rica, Escuela de Administración de Empresas, 2016.
Keywords: Instituto Tecnológico de Costa Rica. Centro Académico San José; Manuales de procedimientos; Análisis administrativo